Một trăm linh một 101 great resumes - Fry, Ron (Career Press, 2002)
Now in a completely revised and updated edition, 101 Great Resumes is a necessary resource for anyone who needs tips on creating that eye-catching resume, or for anyone who simply needs a format to follow. This collection of resumes is designed to appeal to the widest audience possible, by covering the greatest range of formats, personal situations, and careers. And in a job market that The New York Times called "the worst for college graduates in nearly a decade," one in which "the job candidate is no longer calling the shots," people need all the help they can get!